Effects of corticotrophin-releasing factor receptor 1 antagonists on amyloid-β and behavior in Tg2576 mice - Dong, Hongxin (Psychopharmacology (Berl), 2014)
RATIONALE: Previous studies indicate that psychosocial stressors could accelerate amyloid-β (Aβ) levels and accelerate plaque deposition in mouse models of Alzheimer disease (AD). Stressors enhanced the release of corticotrophin-releasing factor (CRF) and exogenous CRF administration mimicked the effects of stress on Aβ levels in mouse models of AD. However, whether CRF receptor 1 (CRF1) antagonists could influence the stress-induced acceleration of an AD-like process in mouse models has not been well studied. OBJECTIVE: We sought to examine whether CRF1 antagonists inhibit the effects of isolation stress on tissue Aβ levels, Aβ plaque deposition, and behaviors related to anxiety and memory in Tg2576 mice, and to investigate the molecular mechanism underlying such effects. METHODS: Cohorts of Tg2576 mouse pups were isolated or group-housed at 21 days of age, then the subgroups of these cohorts received daily intraperitoneal injections of the CRF1 antagonists, antalarmin or R121919 (5, 10 and 20 mg/kg), or vehicle for 1 week. Other cohorts of Tg2576 mouse pups were isolated or group housed at 21 days of age, and then at 4 months of age, subgroups of these mice were administered antalarmin (20 mg/kg) or vehicle in their drinking water for 6 months. Finally, cultured primary hippocampal neurons from regular Tg2576 pups (P0) were incubated with CRF (0.1, 1 and 10nM), antalarmin (100 nM) or H-89 (1 μM) for 48 hours. Brain tissues or cultured neurons were collected for histological and biochemical analyses, and behavioral measures were collected in the cohorts of mice that were chronically stressed. RESULTS: Administration of antalarmin at 20 mg/kg dose for 1 week significantly reduced Aβ(1-42) levels in isolation stressed mice. Administration of antalarmin for 6 months significantly decreased plasma corticosterone levels, tissue Aβ(1-42) levels and Aβ plaque deposition in the brain and blocked the effects of isolation stress on behaviors related to anxiety and memory. Finally, incubation of neurons with 100 nM antalarmin inhibited the ability of 10 nM CRF to increase Aβ(1-42) levels and protein kinase A IIβ (PKAIIβ) expression. The effect of CRF1 on Aβ(1-42) levels was also diminished by treatment with H-89, a c-AMP/PKA inhibitor. CONCLUSIONS: These results suggest that CRF1 antagonists can slow an AD-like process in Tg2576 mice, and that the c-AMP/PKA signaling pathway may be involved in this effect.